Performance of Patients with Early Parkinson Disease on an Executive and Social Cognition Battery. Issue 3 (September 2018) - Esteves, Sol; Gleichgerrcht, Ezequiel; Torralva, Teresa; Chade, Anabel; Gómez Arévalo, Gonzalo; Gershanik, Oscar; Manes, Facundo; Roca, María
Abstract : Objective: To demonstrate the usefulness of incorporating the Executive and Social Cognition Battery (ESCB) to detect executive and social cognition deficits, which are otherwise not captured by more "classical" executive tests in early Parkinson disease (PD). Background: PD is a neurodegenerative disorder that includes executive and social cognition deficits. While cognitive assessment in PD still relies on classical executive tasks to detect frontal deficits, these traditional tests often fail to uncover subtle, yet relevant, frontal impairment. Methods: We evaluated 39 PD patients and 47 controls with a battery of classical executive tests and the ESCB. The ESCB includes a series of tasks that more closely resemble real-life activities and have been previously shown to be useful in detecting executive deficits in other neuropsychiatric disorders with frontal involvement. Results: We observed that both batteries used in a complementary way yielded better results, as 15 of the 39 patients presented deficits only on some of the ESCB tests, but not on the classical battery, while 5 patients presented deficits only on some tests of the classical battery, but not on the ESCB. Fourteen patients presented deficits on some tests of either battery, and 5 patients did not present deficits on any of the tests. Conclusions: We found that, used along with traditional neuropsychological tasks, the ESCB may be useful in providing a more comprehensive evaluation of frontal dysfunction among patients with PD, thus contributing to the early diagnosis of cognitive disorders in this patient population. Abstract : Supplemental Digital Content is available in the text.